Corporate Shares as Shares - Katz, Larissa (Modern Studies in Property Law, 2019)
In this chapter, I ask whether shares in corporations ought to command more attention within theories of property. Contemporary liberal property theorists typically take land (and sometimes goods) as the basic case of property. Shares tend to be left out of these accounts or treated as imitations or mutations of the basic case. Economists, for their part, have transformed the idea of ownership: ‘owner’ refers to the ultimate beneficiary of the value of assets. Shares are treated as a central case of property by those who take this approach. Shareholders are taken to own the corporation insofar as they are the ultimate beneficiaries of its value. In this chapter, I concede shares do not fit within the traditional property framework. This does not mean, however, that the traditional idea of property is obsolete and that a new property framework is in order.
Accepted: 2023-06-22T17:00:40Z ISBN: 9781509921379 Publisher: Hart Publishing

Abuse of legal personality to avoid tax : piercing the corporate veil as remedy in case of the abuse of legal personality for tax purposes - Marais, Albertus Johannes (Stellenbosch University, 2019)
Companies are legal persons and as much part of commercial traffic as the natural persons owning and controlling them. Compared to one another, companies and natural persons nevertheless have very different legal abilities and characteristics. It is therefore not unexpected that they are treated differently for purposes of the law of taxation. As a result it may often be more beneficial to have the profits generated by a business enterprise taxed in a company rather than in the hands of a natural person, especially in instances where a shareholder would be commercially indifferent to whether those profits are generated in a company or not. By using the separate legal personality of a company shareholders may often perpetrate an abuse of that separate legal personality. Such abuse of legal personality can also take place when legal personality is employed primarily for tax reasons. While a limited form of abuse of the corporate veil is tolerated, whether the use of separate legal personality for tax reasons amounts to an abuse thereof beyond what is permitted in South Africa can be determined in terms of three tests. These tests are the traditional “piercing of the corporate veil” judgments forming part of the common law, section 20(9) of the Companies Act 71 of 2008 and the General Anti-Avoidance Rules (“GAARs”) (and other specific provisions) in the Income Tax Act 58 of 1962. This dissertation considers when any of these various tests will dictate that the separate personality of a company be ignored (or “pierced”) for purposes of taxes levied in terms of the Income Tax Act. Through critical analysis of both the South African rules on piercing as applied for tax purposes as well as the circumstances under which selected other jurisdictions provide for piercing for tax reasons the dissertation formulates what best practice and desired policy for piercing for tax reasons are.
URI: http://hdl.handle.net/10019.1/106096
Keywords: Close Corporations Act; 1984; Companies Act; 2008; Corporate veil; Corporations; Income Tax Act; 1962; South Africa; Tax evasion; Taxation; Unconscionable abuse

Regulation of takeovers and mergers with an emphasis on the mandatory offer rule: a comparative and critical analysis of the law and the institutions that have been set up to enforce the law - Phakeng, Madimetja A. L. (Stellenbosch University, 2019)
ENGLISH ABSTRACT :This dissertation assesses the regulation of takeovers and mergers and the institutions created to enforce the law, from a comparative perspective. It uses South Africa as its point of departure and takes the laws of Delaware in the United States, the United Kingdom and Australia into account. The dissertation indicates that numerous takeover provisions in South Africa are poorly formulated, making them difficult to interpret and apply. Accordingly, the dissertation recommends amendment and improvement of certain Takeover Provisions. Special emphasis is placed on the mandatory offer requirement. The dissertation critically and comparatively analyses this requirement and especially its impacts on the market for corporate control, efficient usage of capital, corporate governance and (in South Africa) Broad Based Black Economic Empowerment. It appears from the literature explored that the mandatory offer requirement originated from the Perlman case in the United States as an expression of the equal opportunity rule. According to the equal opportunity rule, the controlling stake of a company is enriched with a premium of control, which must be shared with other shareholders when there is a change of the controlling shareholder. Shareholders must be given an equal opportunity to share in this control premium. Hence, a mandatory offer must be made to the remaining shareholders of the company by the new controlling shareholder at a price at which control was bought. Perlman case was decided in the United States of America during 1955. It is contended in the dissertation, that the mandatory offer requirement in section 123 of the Companies Act 71 of 2008 (“the Act”), can ultimately be traced back to this case. Researchers have criticised the mandatory offer requirement in a number of respects. It has been pointed out that the rationale for the decision in the Perlman case was not clear and applied in limited circumstances. Other scholars point out that the case was not a final decider on the sharing of the control premium due to later judicial pronouncements that differed with that case. Despite these commentaries, it appears that the case became a basis for imposing and enforcing this most debated rule in takeover and merger law. The dissertation concludes that the sharing of a premium of control, as envisaged by the mandatory offer requirement, is not enforced in the state of Delaware. It further concludes that in the UK, the mandatory offer rule forms the cornerstone of enforcement of the equal opportunity rule, but that widely dispersed shareholding ameliorates it negative consequences in that jurisdiction. The dissertation favours the Australian approach. That jurisdiction does not require a mandatory offer similar to that in section 123 of the Act, but, Australian Takeover Provisions, unlike their South African equivalent, have been tailor-made for Australian market conditions. The dissertation accordingly concludes that the mandatory offer requirement in section 123 of the Act in its current form is not appropriate for South Africa.
URI: http://hdl.handle.net/10019.1/105995
Keywords: Consolidation of corporations; Delaware; Great Britain; Merger of corporations; Regulation; South Africa